Establishment of a new canine cell line (CCT) originated from a cutaneous malignant histiocytosis - Sakai, H. (Gifu Univ. (Japan). Faculty of Agriculture); Nakano, H; Yamaguchi, R; Yonemaru, K; Yanai, T; Masegi, T (Journal of Veterinary Medical Science, 2003)
A new canine cell line, named CCT, was established from the cutaneous malignant histiocytosis in a 4-year-old male Borzoi. CCT proliferated with loose adherence and doubling time was approximately 30 hr. When co-cultured with latex beads, CCT phagocytized beads vigorously. Lysozyme and vimentin were positive by immunostaining, and non-specific esterase and acid phosphatase were positive by cytochemical staining. These features indicated the cells had a histiocytic nature. Furthermore, by subcutaneous injection to nude mice CCT could successfully form tumors with the morphological and immunohistochemical features similar to the original tumor.